University rankings theoretical basis, methodology and impacts on global higher education - Shin, Jung Cheol; Toutkoushian, Robert Kevin, 1962-; Teichler, Ulrich (The changing academy- the changing academic profession in international comparative perspective ;)
While university ranking surveys are widely used in policy and academic discussions, this is the first book to explore the theoretical and methodological issues of ranking itself. It is a much-needed reality check on the many problems inherent in the surveys.